2014
DOI: 10.2141/jpsa.0140032
|View full text |Cite
|
Sign up to set email alerts
|

Left-Right Asymmetry in Chicken Embryonic Gonads

Abstract: Avian embryos have reproductive organs with unique characteristics. In female, the gonads develop asymmetrically: the left gonad generates a functional ovary, whereas the right gonad and associated embryonic oviduct (Müllerian duct) regress. In males, however, both left and right gonads develop into testes. Recent evidence, however, revealed that left-right asymmetry can be detected in both sexes. Even male embryos have a greater number of germ cells in the left gonad. Moreover, pluripotency-associated markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
3
0
1
Order By: Relevance
“…It suggests that the two testes are functionally different, with the left being more functional than the right. Recent studies have shown that after gonadal differentiation, stem cell numbers, and gene expression profiles are higher in the left gonad in both sexes (Intarapat and Stern , ). This difference in early development may translate into a functional difference in adulthood, resulting in a higher functionality in the left gonad in both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that the two testes are functionally different, with the left being more functional than the right. Recent studies have shown that after gonadal differentiation, stem cell numbers, and gene expression profiles are higher in the left gonad in both sexes (Intarapat and Stern , ). This difference in early development may translate into a functional difference in adulthood, resulting in a higher functionality in the left gonad in both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…The cortex is thickened only in the left gonad, and the right one is flattened (Ishimaru et al, 2008;Guioli et al, 2014). In addition, there are a greater number of germ cells in the left gonad (Nakamura et al, 2007;Intarapat and Stern, 2014). The right ovary lacks the thickened cortex, but the cortical region of the left ovary continues to develop; therefore, only germ cells in the left cortex can enter meiosis (Smith et al, 2008), and only the left ovary is functional.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, estrogen and its receptor are asymmetrically expressed in avian embryonic gonads during sexual differentiation Nakabayashi et al, 1998). Asymmetric expression of estrogen and its receptor in chicken embryonic gonads is related to left-right gonadal asymmetry in birds (Intarapat & Stern, 2014).…”
Section: Introductionmentioning
confidence: 99%